Incorporating pinch distillation boundaries into the conceptual modeling of batch distillations: Ternary mixtures - Torres, Karina Andrea (2012)
This contribution explores the influence of curved unstable distillation boundaries on the performance of batch distillations in ternary mixtures and its incorporation into a conceptual modeling framework under the assumption of a batch rectifier with an infinite number of stages. First, the concept of preferred separation in batch distillation is presented. Calculation of "pitchfork" distillation boundaries is then determined using a robust predictor-corrector algorithm based on improved memory method with the purpose of estimating the maximum feasible distillate composition in the preferred separation line. Four highly nonideal systems are studied. Finally, the model is extended to allow simulation of the operation at different reflux policies. Results of a complete simulation performed with the enhanced conceptual model are shown for the system octane/2-ethoxyethanol/ethylbenzene.